Territoires de libération : perspectives féministes musulmanes - Benhadjoudja, Leïla (Tumultes, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discipline; discours dominant; fem3400; féminisme islamique; féminisme musulman; histoire et politique; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques

In the name of women's rights: the rise of femonationalism - Farris, Sara R. (Duke University Press, 2017)
Sara R. Farris examines the demands for women's rights from an unlikely collection of right-wing nationalist political parties, neoliberals, and some feminist theorists and policy makers. Focusing on contemporary France, Italy, and the Netherlands, Farris labels this exploitation and co-optation of feminist themes by anti-Islam and xenophobic campaigns as “femonationalism.” She shows that by characterizing Muslim males as dangerous to western societies and as oppressors of women, and by emphasizing the need to rescue Muslim and migrant women, these groups use gender equality to justify their racist rhetoric and policies. This practice also serves an economic function. Farris analyzes how neoliberal civic integration policies and feminist groups funnel Muslim and non-western migrant women into the segregating domestic and caregiving industries, all the while claiming to promote their emancipation. In the Name of Women's Rights documents the links between racism, feminism, and the ways in which non-western women are instrumentalized for a variety of political and economic purposes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; cours; discipline; europe; france; féminisme islamique; fémonationalisme; histoire et politique; intersectionnalité; italie; justice sociale; pays-bas; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques

"Deveiling" Body Stories: Muslim Girls Negotiate Visual, Spatial, and Ethical "Hijabs" - Hamzeh, Manal (Race, Ethnicity and Education, 2011)
This article describes a collaborative research project that took place in two south‐western US border towns and sought to understand how four muslim Footnote 1 girls (age 14–17) expressed and negotiated their bodily learning experiences. Drawing on both the work of arab–muslim critical feminist Fatima Mernissi who utilized classical Islamic tools of research and my positionalities as arabyyah‐muslimah, I used insider’s methods to discuss how three hijabs (veils) – the visual, spatial, and ethical – acted as a central genderizing discourse that challenged the girls’ learning opportunities. This article shows how the girls’ parents enforced these three hijabs; how the girls questioned and deveiled the hijabs in their dress, mobility in public places, and physical behavior around boys. This inquiry is a call for critical feminist researchers and educators to recognize how these three hijabs form a key genderizing discourse in the lives of muslim girls. It also presents the importance of: (1) working with muslim girls as agents in their own lives; (2) critical engagement with difference between researchers/educators and muslim communities; and (3) practicing a critically reflexive pedagogy of deveiling.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; corps; cours; discipline; féminisme islamique; point de vue situé; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; thématiques; états-unis; états-unis (sud)

Ethnocentrisme occidental et perceptions du harem - Ahmed, Leila (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2010)
En 1980, lors de la conférence de la National Women’s Studies Association qui s’est tenue à Bloomington, Indiana, j’ai assisté à une présentation sur « Les femmes dans l’islam » au cours de laquelle je suis intervenue vivement, depuis ma place dans le public, car les intervenantes invitées, trois femmes arabes, présentaient, selon moi un tableau idéalisé de la situation des femmes dans l’islam. Les sociétés islamiques se distinguaient peut-être même plutôt – c’est en tout cas ce que je pensais à l’époque – par le fait qu’elles plaçaient sans équivoque les femmes sous le contrôle des hommes et par le fait qu’elles accordaient aux hommes, de façon tout aussi explicite, le droit à une sexualité et le droit d’exploiter les femmes. Comme le soutenaient les intervenantes, à son avènement l’islam avait apporté un certain nombre de progrès positifs pour les femmes en Arabie. Il avait également accordé certains droits aux femmes tels que le droit à la propriété (qui, en Occident, ne fut accordé aux femmes qu’au dix-neuvième siècle et qui n’est d’ailleurs toujours pas accordé aux femmes selon, parexemple, la loi rabbinique, tout comme le droit de témoigner). Et on ne pouvait certainement pas dire que l’islam était plus malveillant à l’égard des femmes que les deux autres religions monothéistes. Cependant, il me semblait que cela ne justifiait en rien le fait de minimiser la position d’approbation flagrante qui est celle de l’islam en ce qui concerne la supériorité des hommes et le contrôle exercé par ces derniers sur les femmes. Ni d’ailleurs le fait d’occulter les difficultés rencontrées par les femmes, en particulier en ce qui concerne les lois sur le mariage, le divorce et la garde des enfants. Cet article est la traduction de : « Western Ethocentrism and Perceptions of the Harem », Feminist Studies, vol. 8, n°3, autumn 1985, p. 521-534. Cet article a été écrit en 1982 donc avant la disparition de l’Union Soviétique qui date de 1992.
Keywords: approches et analyses; asie; cours; discipline; droits des femmes*; fem1000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; occident; orient; premier cycle; rapports de domination; rapports sociaux de sexe; ressource en ligne; régions géographiques; science des religions; sciences humaines; sciences juridiques; sciences sociales; sociologie; stéréotypes; thématiques; voiles islamiques